Attitude and Islamic banking adoption: moderating effects of pricing of conventional bank products and social influence - Mindra, Rachel; Bananuka, Juma; Kaawaase, Twaha; Namaganda, Rehma; Teko, Juma (Journal of Islamic Accounting and Business Research, 2022)
The purpose of this study is to establish the relationship between attitude and the intention to adopt Islamic banking in a Christian-dominated country and whether such a relationship is moderated and boosted by pricing of conventional bank products and social influence. Design/methodology/approach – This study adopts a cross-sectional and correlational design as data were collected between July and September 2019. Data were collected using a questionnaire from a sample of 384 adult individuals with bank accounts in conventional commercial banks from which 300 responded, indicating a response rate of 78%. Findings – The findings of this study indicate that attitude is significantly associated with the intention to adopt Islamic banking. This relationship is moderated and boosted by the pricing of conventional bank products and social influence. The interaction of pricing of conventional bank products with attitude is positive and significantly influence the intention to adopt Islamic banking. The interaction of attitude and social influence is significant but negatively related with the intention to adopt Islamic banking. Research limitations/implications – This study uses quantitative data which sometimes misses certain information and limits the respondent’s opinions on the study variables. A mixed method research needs to be conducted on pricing of conventional bank products, social influence, attitude and adoption of Islamic banking to gather the respondent’s opinions on the variables. Practical implications – IB being an alternative source of financing of business in most parts of the world, existing bank customers, international funding agencies and religious leaders could mount pressure on government to speed up the licensing of institutions interested in offering Islamic banking services. Social implications – Uganda being a secular state and having finalized Islamic banking laws in early 2018, it is surprising that there is no bank that has so far started offering Islamic banking products. Originality/value – This study provides an initial empirical evidence from a Christian-dominated country on the moderating effect of pricing of conventional bank products and social influence in the relationship between attitude and intention to adopt Islamic banking.
Keywords: Islamic banking; Attitude; Pricing; Social influence; Conventional banking